EFICIÊNCIA DO P ENERGETIC® NA CULTURA DO ALGODOEIRO - COSTA, Victor Souza; GREITER, Luiz Mateus Gonçalves; LOPES, Fernando de Souza; MALDONADO, Eduardo da Cunha; SILVA, Pablo Rozo; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-